2019
DOI: 10.1101/634808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Frontal theta and beta oscillations during lower-limb movement in Parkinson’s disease

Abstract: Background: Motor function and aberrant cognition have been linked in patients with Parkinson's disease (PD), but it is unknown if these are distinct symptoms or if they are correlated outcomes of a single dysfunctional latent process. EEG theta and beta rhythms are reliably associated with cognitive and motor functions, respectably. We tested the hypothesis that PD patients with lowerlimb abnormalities would exhibit abnormal beta and theta rhythms in the mid-frontal region during action initiation. Methods:We… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(62 citation statements)
references
References 62 publications
3
59
0
Order By: Relevance
“…Complex cellular factors such as alpha-synuclein and deficits in ascending neurotransmitter systems contribute to PD 11,35 . Despite this complexity, these cellular processes lead to neurophysiological phenomena observable by scalp EEG and intracortical recordings, which have been enormously helpful in both designing medical therapies and targeting brain stimulation sites to address the motor symptoms of PD 33,[36][37][38] . Our results are significant in advancing our neurophysiological understanding of cognitive function in PD because we link PD-related cognitive dysfunction (as measured by MOCA) to midfrontal~4 Hz rhythms, which are a putative cognitive-control mechanism 23 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complex cellular factors such as alpha-synuclein and deficits in ascending neurotransmitter systems contribute to PD 11,35 . Despite this complexity, these cellular processes lead to neurophysiological phenomena observable by scalp EEG and intracortical recordings, which have been enormously helpful in both designing medical therapies and targeting brain stimulation sites to address the motor symptoms of PD 33,[36][37][38] . Our results are significant in advancing our neurophysiological understanding of cognitive function in PD because we link PD-related cognitive dysfunction (as measured by MOCA) to midfrontal~4 Hz rhythms, which are a putative cognitive-control mechanism 23 .…”
Section: Discussionmentioning
confidence: 99%
“…This effort will also require systematic clinical studies using EEGbased biomarkers to assess the usefulness of~4 Hz rhythms in diagnosing cognitive dysfunction, which is often underrecognized in the clinical setting 50 . Of note, we focus on~4 Hz based on extensive human work in PD and cognitive control as well as our animal work [21][22][23]25,28,33 . While~4 Hz deficits may not be highly predictive of PD, our work suggests that interval-timing variability and~4 Hz deficits are predictive of cognition in PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach involves the evaluation of frequency bands (25, 94), event-related synchronization (ERS), and desynchronizations (ERD) (95), as well as information flow to examine how a physical manifestation can be correlated to a neural occurrence. In the work by Singh et al, theta and beta bands were evaluated during lower-limb pedaling in PDFoG+ and PDFoG- (96). Results from this study showed that compared to PDFoG-, PDFoG+ exhibited an attenuated mid-frontal theta (4-8 Hz) power, which is associated with impairments in cognitive control (97,98).…”
Section: Cortical Levelmentioning
confidence: 77%
“…In terms of EEG frequency band analysis, the beta band was shown to increase in the frontal region during lower limb pedaling in PDFoG+, indicating preparatory adjustments and motor plan execution through top-down signaling (118). Also, for PDFoG+ theta band power was attenuated in the mid-frontal location, indicating an impairment in cognitive control (96). In the study that used the dual-task oddball paradigm, although the stimulus was detected by an increased P300, beta ERD was unchanged for PDFoG+.…”
Section: Summary Of Findingsmentioning
confidence: 93%